Advanced Techniques and Applications in Magnetic Resonance Spectroscopy for Pediatric Patients - Tamrazi, Benita (Journal of Pediatric Neurology, 2018)
Magnetic resonance spectroscopy (MRS) is a noninvasive tool that is often used in conjunction with conventional MR imaging to acquire information regarding the biochemistry of tissue. In pediatric patients, the traditional clinical application of MRS was in the preoperative diagnostic workup of brain tumors. In recent years with the boom of molecular testing, MRS application for tumor evaluation is becoming more advanced, now potentially serving as a biomarker for molecular subgroup classification. This article will review MRS techniques as well as clinical applications, both conventional and more advanced applications in the pediatric population including tumor assessment, hypoxic-ischemic injury, abusive head injury, and autism.
Keywords: MR spectroscopy; pediatric brain tumors; hypoxic-ischemic encephalopathy; abusive head injury; autism